Implementation of the Good Behavior Game Method to Improve Interpersonal Mindfulness Skills of 2024 KKN Students at Bhakti Kencana University in Nanjung Village, West Java - Widyastuti, Linda; Nurlatifah, Azzahra Siti; Rambe, Ira Hasiana; Adhitia, Rifan; Dahliah, Dedeh (International Journal of Humanities, Law, and Politics, 2025)
The interpersonal mindfulness program is an activity carried out to deepen insight into healing and realizing what is detrimental to oneself by being guided either in pairs or small groups. Habituating someone to behave, especially in the use of interpersonal mindfulness, requires more directed and regular activities. Good behavior game (GBG) is one of the activities used as a class or group management strategy in which there are activities or activities containing rules, dividing groups, providing feedback, deducting points if anyone violates the rules. The results of the literature search show several studies related to this theme in the form of good behavior game methods that can affect individual self-regulation. The research design uses a Pre-Experimental design with One Group Pre-Post Design method. The study will be conducted on 23 students who are doing the Community Service Program (KKN) in Nanjung Village. Based on the research results, there was a 4.52% increase in interpersonal mindfulness among students. However, the results of this statistical test showed that the implementation of the Good Behavior game was not considered effective in increasing Interpersonal Mindfulness in KKN students. This can still show an initial indication of the program's success, even though it is on a small scale. This can be caused by several things such as good behavior game which focuses more on disruptive behavior, while mindfulness is more on the individual's abilities within themselves, and the duration of the activity is considered insufficient to create habituation in its rules. Although from the students' opinions, they feel that they have learned to communicate well and understand other people.